PENERAPAN DEMONSTRASI INTERAKTIF PADA PEMBELAJARAN IPA TENTANG SIFAT-SIFAT BENDA PADAT DAN CAIR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II DI SDN KEPATIHAN 03 KECAMATAN KALIWATES KABUPATEN JEMBER - Anik Supraptianingsih (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract: This research is conducted based the fact that student learning outcomes in science subjects have not yet reached the minimum completeness criteria. The reason of this condition is the learning process carried out by the teacher still uses conventional learning methods. Based on the fact, one of the efforts to improve student learning outcomes in natural science learning about the properties of solid and liquid objects is implementation an interactive demonstration method. The purpose of this study is to describe the implementation of learning by applying interactive demonstration methods in improving the learning outcomes of natural sciences about the properties of solid and liquid objects in class II B students at Kepatihan 03 Elementary School Kaliwates, Jember, academic year 2017/2018. The subjects of this study were class II B students, amounting to 29 children. Class II B student learning outcomes have increased from pre-cycle to second cycle. Classically in the pre-cycle of 58.62%, while in cycle one increased to 72.41%, and in cycle two increased to 86.21%. Based on the results, it can be concluded that the implementation of interactive demonstration methods in natural science subjects the topic of the properties of solid and liquid objects can improve student learning outcomes in grade II B SDN Kepatihan 03 Jember District Kaliwates Jember 2017/2018 school year.